Network meta-analysis of pharmacological treatment for antibody-mediated rejection after organ transplantation - Sun, Junjie; Yu, Yanqing; Huang, Fu; Zhang, Qiuwen; Zhu, Lirong; He, Guining; Li, Haibin; Sun, Xuyong (Frontiers in Immunology, 2024)
ObjectiveThis study aims to assess the efficacy of pharmacological interventions in mitigating graft injury in transplant patients with antibody-mediated rejection (AMR) through a network meta-analysis (NMA).MethodsA search was conducted on databases such as Cochrane Library, PubMed, EmBase, and Web of Science for randomized controlled trials (RCTs) on pharmacological interventions for alleviating graft injury following AMR. The search was performed for publications up to April 12, 2024. Two reviewers conducted independent reviews of the literature, extracted data, and assessed the risk of bias (ROB) in the included studies using the ROB assessment tool recommended by the Cochrane Handbook for Systematic Reviews of Interventions 5.1.0. A Bayesian NMA was conducted using R 4.4.0, RStudio software, and the GeMTC package to assess the outcomes in estimated glomerular filtration rate (eGFR), mean fluorescence intensity (MFI), g-score, and infection under pharmacological treatments.ResultsA total of 8 RCTs involving 215 patients and 6 different pharmacological treatments were included in this NMA. The results indicated that the increase in eGFR by eculizumab (SUCRA score: 81) appeared to be more promising. The decrease in MFI by bortezomib (SUCRA score: 72.3), rituximab (SUCRA score: 68.2), and clazakizumab (SUCRA score: 67.1) demonstrated better efficacy. The decrease in g-score by eculizumab (SUCRA score: 74.3), clazakizumab (SUCRA score: 72.2), and C1INH (SUCRA score: 63.6) appeared to have more likelihood. For infection reduction, clazakizumab (SUCRA score: 83.5) and bortezomib (SUCRA score: 66.8) might be better choices.ConclusionThe results of this study indicate that eculizumab has the potential to enhance eGFR and reduce g-score. Bortezomib demonstrates superior efficacy in reducing MFI. Clazakizumab appears to be more effective in reducing infections.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024546483.